Penerapan Teknik Self Management Untuk Menurunkan Kejenuhan Belajar Siswa Kelas VII - Faradisa, Nidia Fullah (UNIB Press, 2024)
Students with learning boredom feel that the knowledge and skills obtained through learning are not progressing. KSaturation can also occur because students' learning processes have reached the limits of their physical abilities due to boredom and fatigue. One of the efforts through individual counseling with self-management techniques is expected to be able to reduce learning boredom for class VII students in Gresik. The technique for implementing this activity uses individual counseling with self-management techniques for related parties. Observations were carried out by digging up information and observing students' conditions in class by distributing questionnaires for the pre-test. From the results of interviews and observations with guidance and counseling teachers and homeroom teachers, there were several categories of students selected. Each class is represented by 6 students who experience learning boredom. There are 36 people from 3 classes. The decrease in learning boredom of selected class VII students can be observed through student learning outcomes each semester.